Structural characterization of an ionic liquid in bulk and in nano-confined environment using data from MD simulations - Vučemilović-Alagić, Nataša; Banhatti, Radha D.; Stepic, Robert; Wick, Christian; Berger, Daniel; Gaimann, Mario U.; Baer, Andreas; Harting, Jens; Smith, David M.; Smith, Ana-Suncana (Data in Brief, 2020)
This article contains data on structural characterization of the [C2Mim][NTf2] in bulk and in nano-confined environment obtained using MD simulations. These data supplement those presented in the paper “Insights from Molecular Dynamics Simulations on Structural Organization and Diffusive Dynamics of an Ionic Liquid at Solid and Vacuum Interfaces” [1], where force fields with three different charge methods and three charge scaling factors were used for the analysis of the IL in the bulk, at the interface with the vacuum and the IL film in the contact with a hydroxylated alumina surface. Here, we present details on the construction of the model systems in an extended detailed methods section. Furthermore, for best parametrization, structural and dynamic properties of IL in different environment are studied with certain features presented herein.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Interface-normal number density; Ionic liquid; Molecular dynamics simulations; Nanoconfinement; Radial distributions